Efficacy and side effects of baclofen and the novel GABAB receptor positive allosteric modulator CMPPE in animal models for alcohol and cocaine addiction - Vengeliene, Valentina; Spanagel, Rainer (Psychopharmacology, 2018)
Preclinical studies suggest that the GABAB receptor is a potential target for treatment of substance use disorders. However, recent clinical trials report adverse effects in patients treated with the GABAB receptor agonist baclofen and even question efficacy. How can the discrepancy between preclinical and clinical findings be explained?
Gesehen am 09.12.2020